A organização da escola: o diretor e seu trabalho - Antunes, José Adilson Santos; Cunha, Jorge Luiz da (Linguagens & Cidadania, 2017)
This article is so simple and clear, present the work of a school principal in the interests of management and commitment to education and learning. It is necessary to establish, for this, a relationship between work and school in order to refer to the commitment of what historically has been seen in contemporary capitalist society, the formation of human capital to the labor market. In seeking a new paradgm of management,all committed to the educational process, it is thought to relate the work of the school principal with the other actors of the educational process, including it as an employee education.